Brand Switching Produk Kosmetik Halal: Ditinjau dari Aspek Daya Tarik Iklan dan Variety Seeking - Khasanah, Uswatun; Cahya, Bayu Tri (IAIN Kudus, 2018)
This study aims to determine the influence of advertising and variations that seek the appeal of Wardah brand cosmetic switching products. This study uses a field research approach using questionnaire, interview, and documentation methods. The sampling technique uses purposive samples which are distributed to 100 female students of IAIN Kudus who have transformed the brand into Wardah cosmetic products. The method of data analysis uses multiple regression analysis with SPSS version 16. The results of this study indicate that the variable attractiveness of advertising and varieties seeking have a positive and significant influence on brand diversion. Variable search variables are variables that have a dominant influence on the switching variables of halal cosmetic products.